Thermomechanical characterization of a low viscosity PA66 thermoplastic matrix and associated continuous glass fibre composite under processing conditions. (September 2019) - Péron, Mael; Jacquemin, Frédéric; Casari, Pascal; Orange, Gilles; Bailleul, Jean-Luc; Boyard, Nicolas
Characterizing the thermomechanical properties of thermoplastic resins and associated composites is of outmost importance to understand the development of process-induced stresses. To that extent, the characterization of a low viscosity PA66 matrix is proposed thanks to a homemade volumetric dilatometer named PvT-XT and a dynamic mechanical analyser on a wide temperature range. The PvT-XT results, reported for the first time, permit to identify the evolution of the coefficients of thermal expansion, of crystallization shrinkage and of the bulk modulus with temperature. Dynamic mechanical analyser experiments lead to the estimation of the Young's modulus. The shear modulus as well as the Poisson's ratio are then estimated thanks to analytical relations for isotropic and homogeneous materials. These properties are used to feed a new analytical model estimating the coefficients of thermal expansion of quasi-unidirectional composites. All the results are compared with the values from the literature or from complementary experiments, showing a good agreement which permits to validate the developed methodology.